The Limits of the Self, the Limits of the Mind - Jedynak, Anna (Analiza, racjonalność, filozofia religii: Księga jubileuszowa dedykowana Profesorowi Ryszardowi Kleszczowi. Nr 6 (2020), 2020)
Philosophy sees two trends which position the self, or the mind, as exceeding beyond the typically accepted boundaries. Firstly – as the feeling of oneness with all being, the universe, nature or God, known through different cultures and ages. Romain Rolland called this the “oceanic feeling” and considered it the basis of spirituality. Secondly – as a series of more recent concepts, with a very broad understanding of the mind inclusive of some elements of the surroundings (Extended Mind Theory, the concept of embodied embedded mind, enactivism). Those two trends differ in their approach, origin and method. The oceaning feeling is very personal, felt rather than conceived, affecting the experience of one’s existence. Whereas the aforementioned concepts are objectified, they examine the mind externally, considering rational arguments and neuroscientific testimony. Despite these differences though, both trends focus on similar issues. What is interesting, the gradual radicalisation of the different concepts of an extended mind seems to follow similar stages as the gradual broadening of the sense of self in some types of meditative practice.